ROLE OF COMMUNICATION NETWORKS IN INTERGROUP CONFLICTS - Muhamad Isnaini; Sarwititi Sarwoprasodjo; Rilus A. Kinseng; Kholil Kholil (Profetik: Jurnal Komunikasi, 2020)
The research background relates to the intergroup conflicts involving some street gangs in Johar Baru Sub District, Central Jakarta. Most of the street gangs in Johar Baru Sub District have each territory. Small matters from mocking one another, miscommunication to rumors which jeopardize the power of the street gangs, can trigger a serious thing: brawls with high fatality rate for several days. The research aims to analyze the pattern of rivalry and alliance network established among the street gangs. This study uses a quantitative approach. The research methods analyzed ego-centered communication networks. After analyzing the communication networks, the inter-group mapping was obtained and in turn, it would be useful as a means of a communication intervention to reduce and prevent inter-group conflicts. Data collection was carried out in a kind of a census towards 40 street gangs in Johar Baru Sub-District and it got the support of the in-depth interviews with several key informants. Research results shows: the communication networks analysis reveal that rivalry and alliance among the street gangs have positioned Gembrong street gang as the centre of rivalry and alliance with the radial communication pattern indices of low network density (10.71 for the rivalry network; 0.00 for the alliance network) and low network closure (0.10 for rivalry network and 0.00 for alliance network). This research contributes to identify which groups have a bigger role in intergroup conflicts.